2020
DOI: 10.20965/jrm.2020.p0947
|View full text |Cite
|
Sign up to set email alerts
|

Study on Human Behavior Classification by Using High-Performance Shoes Equipped with Pneumatic Actuators

Abstract: In Japan, accidents involving the falling of elderly people are increasingly becoming a problem. To solve this problem, walking training is effective for preventing falls of elderly people. In this study, a walking training system was developed in which high-performance shoes are used to improve the efficiency of walking training. The high-performance shoes have three functions: 1) measurement of plantar pressure using changes in the inner pressure of the insole, 2) leg movement measurement using a six-axis mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Mat. ), it was observed that many research groups have used their own custom designed insoles [29], [30], where ML-based classification is often used for validation purposes. It was also evident that there is little consistency in the classification techniques employed, as well as the validation and assessment methods [31]- [33].…”
Section: Introductionmentioning
confidence: 99%
“…Mat. ), it was observed that many research groups have used their own custom designed insoles [29], [30], where ML-based classification is often used for validation purposes. It was also evident that there is little consistency in the classification techniques employed, as well as the validation and assessment methods [31]- [33].…”
Section: Introductionmentioning
confidence: 99%